Description of two new species of Haliplectus Cobb, 1913 (Nematoda, Plectida, Haliplectidae) from mangrove areas of Sandspit backwater, Karachi, Pakistan - Waheed, Samina; Decraemer, Wilfrida; Kazi, Nasira; Tariq, Rajput Muhammed; Iqbal, Erum (Zootaxa, 2024)
Haliplectus shahinae n. sp. and H. sandspitensis n. sp. two free-living marine nematodes of the family Haliplectidae Chitwood, 1951 collected from mangrove areas of Sandspit backwater, Karachi, Pakistan, are being described and illustrated. Both new species belong to a group of species characterized by the presence of a bipartite basal esophageal bulb with striated or unstriated valve plates. H. shahinae n. sp. is characterized by its comparatively shorter body length (0.4–0.44 mm); annulated cuticle; amphidial fovea at 6–9 µm from the anterior end; bipartite basal bulb with unstriated valve plates; reproductive system mono-prodelphic with reflexed ovary, presence of post uterine sac and vulva at 52–57% of body length and tail short conoid, straight, 1.5–1.8 times anal body width long. H. sandspitensis n. sp. is characterized by more than 1 mm body length (1.0–1.2 mm); annulated cuticle; amphidial fovea at 8–12 µm from the anterior end; bipartite basal bulb with striated valve plates; didelphic reproductive system, with the vulva at 40–47% of body length and tail elongated, conoid, 1.4–2.2 times anal body width long. A dichotomous identification key is provided for the valid species of Haliplectus Cobb, 1913.